LMNA-related muscular dystrophy: Identification of variants in alternative genes and personalized clinical translation - Cesar, Sergi; Coll, Monica; Fiol, Victoria; Fernandez-Falgueras, Anna; Cruzalegui, Jose; Iglesias, Anna; Moll, Isaac; Perez-Serra, Alexandra; Martínez-Barrios, Estefanía; Ferrer-Costa, Carles; Olmo, Bernat del; Puigmulè, Marta; et al. (Frontiers in Genetics, 2023)
Background: Laminopathies are caused by rare alterations in LMNA, leading to a wide clinical spectrum. Though muscular dystrophy begins at early ages, disease progression is different in each patient. We investigated variability in laminopathy phenotypes by performing a targeted genetic analysis of patients diagnosed with LMNA-related muscular dystrophy to identify rare variants in alternative genes, thereby explaining phenotypic differences. Methods: We analyzed 105 genes associated with muscular diseases by targeted sequencing in 26 pediatric patients of different countries, diagnosed with any LMNA-related muscular dystrophy. Family members were also clinically assessed and genetically analyzed. Results: All patients carried a pathogenic rare variant in LMNA. Clinical diagnoses included Emery-Dreifuss muscular dystrophy (EDMD, 13 patients), LMNA-related congenital muscular dystrophy (L-CMD, 11 patients), and limb-girdle muscular dystrophy 1B (LGMD1B, 2 patients). In 9 patients, 10 additional rare genetic variants were identified in 8 genes other than LMNA. Genotype-phenotype correlation showed additional deleterious rare variants in five of the nine patients (3 L-CMD and 2 EDMD) with severe phenotypes. Conclusions: Analysis f known genes related to muscular diseases in close correlation with personalized clinical assessments may help identify additional rare variants of LMNA potentially associated with early onset or most severe disease progression.